2020
DOI: 10.1016/j.fertnstert.2020.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Is Covid-19 a Sexually Transmitted Disease? A Systematic Review

Abstract: OBJECTIVE: To assess the efficacy and safety of LGX, an oral GnRH receptor antagonist, administered with and without hormonal add-back therapy (ABT: 1 mg estradiol/0.5 mg norethindrone acetate), for the treatment of HMB and other symptoms of UF.DESIGN: PRIMROSE 1 (USA, n¼526) and PRIMROSE 2 (Europe and USA, n¼511) are randomized, double-blind, placebo-controlled Phase 3 trials, with essentially identical design, investigating the efficacy and safety of LGX AE ABT once daily for 52 weeks. We report results up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In contrast, other studies failed to document viral transmission in semen samples from men with active SARS-CoV-2 infection or during the convalescence period suggesting a remote possibility for viral transmission during ART treatments [ 3 , 4 ]. In a systematic review, only 1 out of 7 studies found positive SARS-CoV-2 RNA tests in seminal fluid (6 out of 143 total men) [ 5 ]. Therefore, the debate is still going on but it seems that the transmission rate of the infection through semen is negligible, if any.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies failed to document viral transmission in semen samples from men with active SARS-CoV-2 infection or during the convalescence period suggesting a remote possibility for viral transmission during ART treatments [ 3 , 4 ]. In a systematic review, only 1 out of 7 studies found positive SARS-CoV-2 RNA tests in seminal fluid (6 out of 143 total men) [ 5 ]. Therefore, the debate is still going on but it seems that the transmission rate of the infection through semen is negligible, if any.…”
Section: Discussionmentioning
confidence: 99%
“…Manifold transmission ways have been reported: via droplets, surfaces, via inanimate objects, fecal–oral transmission, and biological fluids transmission (saliva, tears), notwithstanding that vertical transmission is also a hypothesis largely debated. Semen transmission presumption cannot be ruled out yet [ 3 ], but a recent systematic review concluded that there is no evidence suggesting that COVID-19 is a sexually transmitted disease (STD) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for the sexual transmission of SARS-CoV-2, the vaginal fluid of a patient diagnosed with COVID-19 was positive for SARS-CoV-2 using the reverse transcription polymerase chain reaction [40]. However, COVID-19 is not characterized as a sexually transmitted disease [41]. The oral cavity could also be a potential route for SARS-CoV-2 infection since the virus was detected in saliva samples of patients with COVID-19 [42].…”
Section: Transmissionmentioning
confidence: 99%